Efek Senam dan Progressive Muscle Relaxation terhadap Tekanan Darah dan Kadar Gula Darah pada Lansia - Roh Hastuti Prasetyaningsih; Andreany Kusumowardani (Jurnal Keterapian Fisik, 2020)
Background: The raise of aging population increases the risk of non infectious illness, as hypertensionand diabetes mellitus. A comprehensive treatment consists of pharmacological and non pharmacologicalapproach is required to control and cure those diseases. Gymnastics and Progressive Muscle Relaxationas a method of non pharmacological intervention has been denote to be beneficial to control bloodpressure and glucose level so that improved the outcome of hypertension and diabetes mellitus. The goalof this study was to determine the impact of gymnastics and Progressive Muscle Relaxation on bloodpressure and glucose level of the elderly at Posyandu Lansia Madoh, Boyolali district. Methods: Themothods used a quasi experimental with two group pre-test post-test design. Sample inclusion criteria areelderly aged 50 years or older and willing to be a research sample. As many as 26 sampel that can followthe full intervention.The hypothesis testing uses Mann Whitney Test. Results: Based on the hypothesis testthat blood pressure values obtained p = 0.626 and blood sugar levels p = 0.590. Thus it can be concludedthat gymnastics and PMR are more effective in lowering blood sugar levels than blood pressure.Conclusions: Gymnastics and Progressive Muscle Relaxation has a positive influence on blood sugarlevels than blood pressure. So it needs to be done routinely and scheduled in Posyandu Elderly activitiesin Ngesrep Village, Ngemplak District, Boyolali Regency